Predictive power of nuclear-mass models - Yu. A. Litvinov; A. Sobiczewski; E. A. Cherepanov (Ядерна фізика та енергетика)
Ten different theoretical models are tested for their predictive power in the description of nuclear masses. Two sets of experimental masses are used for the test: the older set of 2003 and the newer one of 2011. The predictive power is studied in two regions of nuclei: the global region (Z, N ≥ 8) and the heavy-nuclei region (Z ≥ 82, N ≥ 126). No clear correlation is found between the predictive power of a model and the accuracy of its description of the masses.